2013
DOI: 10.1128/mbio.00281-13
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin-Resistant Enterococcus faecalis Diverts the Antibiotic Molecule from the Division Septum and Remodels Cell Membrane Phospholipids

Abstract: Treatment of multidrug-resistant enterococci has become a challenging clinical problem in hospitals around the world due to the lack of reliable therapeutic options. Daptomycin (DAP), a cell membrane-targeting cationic antimicrobial lipopeptide, is the only antibiotic with in vitro bactericidal activity against vancomycin-resistant enterococci (VRE). However, the clinical use of DAP against VRE is threatened by emergence of resistance during therapy, but the mechanisms leading to DAP resistance are not fully u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
231
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(248 citation statements)
references
References 47 publications
13
231
1
3
Order By: Relevance
“…66 However, in the liposome model at least, CL inhibits membrane permeabilization, 66 which suggests that it might mediate resistance to daptomycin by competing for it with PG. Such an effect has indeed been claimed to occur in vivo, 67 but the CL-enriched membrane domains purported in that study were identified by staining with nonyl-acridine orange, which has since been shown to bind to phosphatidylglycerol also. 68 Thus, no conclusive evidence is available to support a preferential interaction between daptomycin and CL in vivo (see also section 12).…”
Section: Lipid Specificitymentioning
confidence: 77%
“…66 However, in the liposome model at least, CL inhibits membrane permeabilization, 66 which suggests that it might mediate resistance to daptomycin by competing for it with PG. Such an effect has indeed been claimed to occur in vivo, 67 but the CL-enriched membrane domains purported in that study were identified by staining with nonyl-acridine orange, which has since been shown to bind to phosphatidylglycerol also. 68 Thus, no conclusive evidence is available to support a preferential interaction between daptomycin and CL in vivo (see also section 12).…”
Section: Lipid Specificitymentioning
confidence: 77%
“…Therefore, CL molecules may direct CAMP, or cell division components, to specific microdomains to increase bacterial resistance, or coordinate membrane fission with OM lipid A and PG remodeling. In support of a role for CL in CAMP resistance, vancomycin-resistant Gram-positive Enterococcus faecalis can clinically acquire daptomycin resistance by sequestering CAMP to distinct negatively charged CL microdomains within the plasma membrane (33). In addition, electron micrographs of antimicrobial peptides interacting with bacterial surfaces have captured initial membrane-active events (34).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of DAP is dependent not only on the quantity of binding but also on the quality of binding, as some ␤-lactams induce marked increases in DAP surface binding but do not increase DAP potency. This feature has been recently highlighted in the mechanism of DAP resistance in Enterococcus faecalis, whereby DAP is bound and diverted to membrane sites away from the septum and, therefore, bound drug is sequestered to a site where it is functionally inactive in killing the bacterium (35). NAF, which is considered to be the optimal agent against serious methicillin-susceptible S. aureus infections, appears to exhibit a "best of both worlds" phenotype of potentiating the activity of both DAP and LL37.…”
Section: Discussionmentioning
confidence: 99%